EVALUATION OF CHARACTER EDUCATION PROGRAMS IN STATE VOCATIONAL HIGH SCHOOLS IN SOUTH TANGERANG USING THE DESCREPANCY MODEL - FASIKHI, Fasikhi; BUNYAMIN, Bunyamin; MULJONO, Hery (Journal of Education and Leadership in Education, 2024)
Character education for vocational schools has significant benefits, including making students more independent, responsible as well as a tough personality, never giving up, with a good moral mentality will make students have a good personality and strong resistance to adaptation in the world of work. The purpose of this study is to a) evaluate at the design stage of the character education program, b) evaluate the application (installation) of carrying capacity, c). the implementation process whether it is in accordance with the achievement of program objectives, d).The final result (product) or the main target of the program that has been achieved in the implementation of the program, the cost of the character education program in the Field Work Practice (PKL) program at Vocational High Schools in South Tangerang City, South Tangerang is in accordance with the standards set conduct evaluations on, related to character education using the Descrepancy Evaluation Model (DEM) model according to the stages of Design, Installation, Process, Product and Cost. The research method used is qualitative research by conducting questionnaires, interviews with school management, teachers, students, industry, practitioners, and alumni, as well as field observations in the field. The results of this study show that the design aspect is close to 90% achievement, the installation aspect has 80%-90% achievement, the process aspect has 88% achievement, product 83.82% and cost more than 90%, thus there are gaps at each stage so that comprehensive improvement is needed by exploring and overcoming each criterion that has significant gaps.